On the morality of taking offence. (November 2022) - Parvaresh, Vahid
Abstract: This study explores occasions during which offendees make intuitive judgments about, or offer reasons for, why they feel offended. In this respect, and by drawing on a corpus of online Twitter posts featuring #offended, the study discusses some of the judgments and reasons that offendees most frequently refer to when 'sanctioning' their offence. The study reveals that taking offence involves the offence taker attributing blame to the person who has caused the offence. These attributions of blame appear to be rooted in higher-order moral norms and are typically couched in the format of a complaint about the behaviour in question with a view to causing some remedial action on the part of the person who has caused the offence. Highlights: Taking offence involves a perceived clash between observed and expected behaviour. When we take offence, we attribute some form of blame to the person who has allegedly caused the offence. Interactants' perception of moral norms is an assumed ability. Morally informed norms continue to exert an influence on the taking of offence.